The Egyptian-Ethiopian Relations after the Change (Journal of the College of Education for Women, 2019)
Egypt and Ethiopia have connected in a strong relation as there are historical facts thatdeepen these relations, one of these is Egypt's cooperation in establishing the first economicand financial banking system in Ethiopia.Beside the religious relation between The Egyptian and Ethiopian churches the Nile River isconsidered one of the effective connectionsThat strong then the relations as it leads to some tension between the two countries becauseEthiopia believes that Egypt seeks to control the river tries to build its project over the BlueNile means a threat to the Ethiopian national security.The tension continues even after the revolution of 25th of January 2011because the Nahdadam which is a clear threat for the Ethiopian national security.